Pentingnya Pendidikan Kesehatan dalam Meningkatkan Perilaku Hidup Sehat - Elvi Juliansyah (Journal of Literature Review, 2026)
Health is one of the most important elements in human life in maintaining and preserving their health. The purpose of this study is to describe the importance of health education in improving healthy living behavior. The research method uses a literature review sourced from international and national articles with a descriptive analysis approach. The results of this study indicate that health education using counseling methods, group discussions, counseling, training, demonstrations, print media, electronic media, social media, and a good community-based approach can improve healthy living behavior. The conclusion of this study is that education can improve healthy living behavior of individuals, families and communities.